TRASTUZUMAB-INDUCED RESPIRATORY DISTRESS: A CASE REPORT - Kumar, Nithu M; Sivadas, Akhila; R, Lakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Trastuzumab is a monoclonal antibody effective in treating metastatic breast carcinomas. Cardiotoxicity is the most commonly reported adverse event occurring when used in combination with anthracycline derivatives. Even though pulmonary toxicities are uncommon, immediate withdrawal of the drug is recommended and only reinitiates after the vitals of the patient have become normal. Here, we discuss the case of an 81-year-old female patient who was treated with Injection Trastuzumab for the treatment of breast cancer with metastasis to lungs and received 6 cycles without any major complications. However, 24 h post the last dose; the patient developed a sudden onset of breathlessness and desaturation and was intubated in view of severe metabolic and respiratory acidosis. Blood investigations revealed elevated brain natriuretic peptide, aspartate transaminase, and alkaline phosphatase. Her blood and urine cultures were found to be sterile. She was managed with IV antibiotics, nebulizations, IV fluids, and other supportive medications and had improved considerably. However, on the 11th day, her condition had deteriorated and developed bradycardia. The patient could not be revived and died. Review of the patient’s medication did not reveal the presence of any other possible drugs capable of producing pulmonary toxicity. Trastuzumab should be avoided in patients with underlying respiratory or cardiac issues.